Analisis Pertumbuhan Tanaman Padi Varietas IPB 4S pada Media Tanam dengan Tingkat Cekaman Kekeringan Berbeda - N Nasrudin; Efrin Firmansyah (Fapetrik-UMPAR, 2020)
Drought is abiotic stress that can inhibit the growth and yield of rice plants. A simple method to determine the physiological response, growth, and yield of rice is using plant growth analysis. The aim of this research was to study the physiological characters of IPB 4S rice varieties on planting media with different drought stress levels using plant growth analysis. This research used a non-factorial completely randomized design with 6 levels of water percentage from field capacity, namely field capacity, 10% of field capacity, 20%, 30%, 40%, and 50% of field capacity. The treatment was repeated three times so that there were 18 experimental units. Observation of plant growth analysis was carried out by measuring leaf area and plant dry weight at 3 and 8 days after planting. Drought stress 20-50% of field capacity has a net assimilation rate, leaf area index, and plant growth rate 8 weeks after planting lower than drought stress at field capacity up to 10% of field capacity. In general, an increase in drought stress by 20-50% results in a decrease in net assimilation rate, plant growth rate, and leaf area index of 8 weeks after planting. This shows that the IPB 4S variety of rice plants has tolerance to drought stress up to 10% of the field capacity.